Knowledge and eating habits of CrossFit trainees - Oleksiuk, Klaudia; Grot, Martina; Greń, Maria; Grajek, Mateusz; Krupa-Kotara, Karolina (Quality in Sport, 2023)
Introduction. Achieving high performance in sports is the result of many factors, both exo and endogenous. Proper nutrition is the basis of the so-called healthy lifestyle, health care and prevention of diet-related diseases. Physical activity is an extremely important component and carries a number of benefits that affect mental, physical and social well-being. Failure to provide sufficient energy, can lead to decreased performance, delayed recovery processes or loss of muscle mass. The purpose of the study was to assess the knowledge and nutritional habits of CrossFit trainees. Material and methods. 131 people were surveyed; the questionnaire was posted on the CrossFit Poland forum. The survey was voluntary and anonymous. The results were collected in a database in Microsoft Excel 2010 MS Office Package and statistically analyzed using Statistica 12. In the statistical evaluation of the relationship between characteristics, a significance level of p ≤ 0.05 was adopted. Results. In a survey of the knowledge and eating habits of CrossFit trainees, about 50% of respondents declare that they eat regularly. In addition, 50.5% state a moderate level of knowledge about healthy eating, while 33% state a high level. There is a high incidence of dietary supplement intake, accounting for 78.5%. As the frequency of training increases, the amount of supplements consumed increases. Conclusions. A significant part of the study group declares a very good or moderate level of knowledge of rational nutrition, which influences the choice of and regularity of the meals consumed in this group of Crossfit trainers.